Kardiochirurgia dorosłychAssessment of the role of magnesium supplementation in prevention of atrial fibrillation in patients after coronary bypass grafting operations - Waligórski, Szymon; Mirecki, Oktawiusz; Jędrzejczak, Tomasz; Kazimierczak, Arkadiusz; Mokrzycki, Krzysztof; Brykczyński, Mirosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Objectives: The role of magnesium administration in prevention of atrial fibrillation after cardiac surgery remains unclear, as there is conflicting evidence from studies performed so far. This study was designed as a randomized, placebo controlled trial based on a large group of patients. Material and methods: 227 patients undergoing elective coronary operations in our institution were randomized to study (n = 114) or placebo (n = 113) groups. The study group patients received 3 g of magnesium sulfate as an infusion during the operation and then 1g of magnesium sulfate twice daily for five days after the surgery. The control group patients received saline infusion. Results: The levels of serum magnesium were normal in the study group and low in the placebo group on the day of the operation and for the first two postoperative days. Atrial fibrillation occurred in 26 patients (22,8%) in the study group and in 19 (16.8%) in the placebo group. Atrial fibrillation correlated with patients age and the size of the left atrium. Conclusions: 1. Prophylactic magnesium supplementation allows to maintanan its normal serum level in the perioperative period. 2. Prophylactic magnesium supplementation does not reduce the occurrence of atrial fibrillation. 3. We have noted a correlation of atrial fibrillation with advanced age of patients and large diameter of the left atrium.